Indonesian Language Learning Model Using User Personas for Class X4 High School Students - Halimah, H; Malik, Rizaldi; Yulianeta, Y (Jurnal Pendidikan Indonesia, 2024)
Needs analysis is very important to help students in the learning process. But, most teachers don't do needs analysis first because they don't know the way or procedure to analyze students' needs. Therefore, the purpose of this research is conducted to provide an effective way or procedure in understanding students' needs in the use of Indonesian language learning models using User Persona. This research uses descriptive qualitative method with User Persona as the analysis knife. The data collection method used is questionnaire. Furthermore, the data collected will be analyzed by the researcher. The results of the analysis show that students in class X4 have diverse learning model needs in learning Indonesian language. Through the results of this User Persona, researchers can provide recommendations for learning models that are in accordance with the needs of class X4 students. In addition, this research can increase student involvement in the learning process, assist teachers in designing appropriate learning models, and help teachers to better understand students, and can be a reference for other schools to understand student needs in implementing Indonesian language learning models.